An Online Sharing Session on Project-Based Learning: From Theories to Implementations: Pengabdian - Mali, Yustinus Calvin Gai (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Integrating project-based learning into teaching and learning practices is a possible way to innovate the practices in universities in Indonesia. This community service program aims to equip its participants with practical knowledge of project-based learning that they might need when implementing the approach in their teaching instructions. The community service program was in the form of an online sharing session conducted via the Zoom application. The participants of the session were thirty lecturers of the Language Education and Literature Program in the Faculty of Teacher Training and Education at Universitas Jambi. In the online sharing session, the author presented project-based learning principles (i.e., students’ engagement in a project, group collaboration, learning autonomy, and public audience) and real examples of implementations of project-based learning in his language classrooms (i.e., creating a digital poster and doing an English funfair). The presentation was then followed up by a question-and-answer session where the participants asked questions to the author and shared their experiences in implementing project-based learning in their classrooms. Some recommendations for future community service programs and guiding questions for future project-based learning-related research are also presented in this article.